The role of joint interface on tensile-shear fracture strength of friction stir lap diffusion al-to-steel welds - Chen, ZW; Yazdanian, S; Littlefair, G (TWI, 2012)
Friction stir lap diffusion welding (FSLDW) of Al-to-steel experiments were conducted followed by mechanical testing and metallurgical examination of the welds to study the formation of microstructure at the interface region and its effect on fracture strength. It has been found that fracture strength was very sensitive to the distance (Ldis) between the bottom of the pin to the bottom steel plate. When Ldis was sufficiently small at 0.3 mm, interfacial diffusion and subsequent intermetallic formation was insured but the resulting intermetallic outbursts present along the interface represent the case of incomplete metallurgical joint established. As a result, joint strength is low. A slight pin penetration when Ldis  -0.1 mm has been confirmed to provide a significant increase in joint strength where the interface region was a laminate of deformed steel and intermetallics. It has been found that at Ldis  0 mm, a joint was established with a continuous interfacial intermetallic layer and the weld test sample fractured in a ductile manner during in tensile-shear test, resulting in a considerable increase in fracture strength.